Modulating Electrode Kinetics for Discrimination of Dopamine by a PEDOT:COOH Interface Doped with Negatively Charged Tricarboxylate - Meng, Lingyin; Turner, Anthony P. F.; Mak, Wing Cheung (American Chemical Society, 2019)
The rapidly developing field of conducting polymers in organic electronics has many implications for bioelectronics. For biosensing applications, tailoring the functionalities of the conducting polymer’s surface is an efficient approach to improve both sensitivity and selectivity. Here, we demonstrated a facile and economic approach for the fabrication of a high-density, negatively charged carboxylic-acid-group-functionalized PEDOT (PEDOT:COOH) using an inexpensive ternary carboxylic acid, citrate, as a dopant. The polymerization efficiency was significantly improved by the addition of LiClO4 as a supporting electrolyte yielding a dense PEDOT:COOH sensing interface. The resulting PEDOT:COOH interface had a high surface density of carboxylic acid groups of 0.129 μmol/cm2 as quantified by the toluidine blue O (TBO) staining technique. The dopamine response measured with the PEDOT:COOH sensing interface was characterized by cyclic voltammetry with a significantly reduced ΔEp of 90 mV and a 3-fold increase in the Ipa value compared with those of the nonfunctionalized PEDOT sensing interface. Moreover, the cyclic voltammetry and electrochemical impedance spectroscopy results demonstrated the increased electrode kinetics and highly selective discrimination of dopamine (DA) in the presence of the interferents ascorbic acid (AA) and uric acid (UA), which resulted from the introduction of negatively charged carboxylic acid groups. The negatively charged carboxylic acid groups could favor the transfer, preconcentration, and permeation of positively charged DA to deliver improved sensing performance while repelling the negatively charged AA and UA interferents. The PEDOT:COOH interface facilitated measurement of dopamine over the range of 1–85 μM, with a sensitivity of 0.228 μA μM–1, which is 4.1 times higher than that of a nonfunctionalized PEDOT electrode (0.055 μA μM–1). Our results demonstrate the feasibility of a simple and economic fabrication of a high-density PEDOT:COOH interface for chemical sensing, which also has the potential for coupling with other biorecognition molecules via carboxylic acid moieties for the development of a range of advanced PEDOT-based biosensors
Keywords: electrode kinetics; dopamine discrimination; carboxylic acid groups; citrate doping; PEDOT